Odpowiedzi

2010-01-14T13:37:17+01:00
A) x/2=y/3 (*6)
x+2,5=y

6(x/2)=6(y/3)
x=y-2,5

3x=2y
x=y-25/10

x=2/3y
2/3y-y=-25/10

x=2/3y
-1/3y=-25/10

x=2/3y
y=25/10*3/1

x=2/3y
y=75/10

x=2/3*75/10
y=7i1/2

x=150/30=5
y=7i1/2
x=5

b) x/5-y/4=0 (*20)
x/2-y/16=5,5 (*16)

20(x/5)-20(y/4)=0*20
16(x/2)-16(y/16)=16*5,5

4x-5y=0
8x-y=88

4x=5y
-y=88-8x(*-1)

x=5/4y
y=-88+8x

x=5/4(8x-88)
y=8x-88

x=10x-110
y=8x-88

x-10x=-110
y=8x-88

-9x=-110
y=8x-88

x=110/9
y=8(110/9)-88

x=12i2/9
y=97i7/9-88

x=12i2/9
y=9i7/9


c) x+y/3+y/4=-2 (*12)
2x-y/3-3x/4=3/2 (*12)

12x+12(x/3)+12(y/4)=-2*12
12(2x)-12(y/3)-12(3x/4)=12(3/2)

12x+4x+3y=-24
24x-4y-9x=18

3y=-24-16x
15x=18+4y

y=-8-16/3x
15x=18+4(-8-16/3x)

y=-8-16/3x
15x=18-32-64/3x

y=-8-16/3x
15x+21i1/3x=-14

y=-8-16/3x
36i1/3x=-14

y=-8-16/3x
x=-14*3/109=-42/109

y=-8-16/3(-42/109)=-8+224/109
x=-42/109
y=-8+2i6/109
x=-42/109
y=-5i103/109

d) 2x-1/5+3y-2/4=2(*20)
3x+1/5-3y+2/4=0(*20)

20(2x)-20(1/5)+20(3y)-20(2/4)=20(2)
20(3x)+20(1/5)-20(3y)+20(2/4)=20(0)

20x-4+60y-10=40
60x+4-60y+10=0

20x=54-60y
60x+14=60y

x=54/20-3y
60(54/20-3y)+14=60y

x=54/20-3y
162-180y+14=60y

x=2i7/10-3y
-240y=-176

x=2i7/10-3y
y=176/240(skracamy )22/30=11/15

x=2i7/10-3(176/240)=2i7/10-2i2/10=5/10
y=11/15
x=5/10
58 3 58